LAGA (Law games) / Norafiza Mohd Hardi...[et al.] - Mohd Hardi, Norafiza; Razali, Hasyimah; Hasan, Asrol; Abdul Karim, Zatul Himmah (Universiti Teknologi MARA, Kedah, 2018)
Principles of Corporate Compliance OBM340 course is to equip students with the skills and knowledge in understanding the essential elements of the Malaysian '&1.31 system and Company law. The students will learn how to be good at protecting the rights of individuals or organizations. This introductory level course is essentially divided into four different areas. The syllabus starts with the introduction to the overall Malaysian legal system such as the sources of law and the court system. It then covers a range of specific legal areas relating to various aspects of business relating to the law that include the formation and constitution of companies, and the functions, management and conduct of company meetings. The final section tends to instill knowledge and key skills in handling the overall responsibility of legal issues unemployment relationships. These law subjects can be highly theoretical and require students to remember and recall large volumes of information such as precedence, public and international laws and acts, therefore many students find it difficult to be remembered. Law Games or LAGA was developed to help student in memorize the topic they have learnt. The use of this games aims to help students remember what they have learnt as active participation is encouraged. Houghton et al., 2013 discusses educational games as the utilization of games to support teaching and learning. Their role in education is to increase students' motivation and engagement, to improve students' interaction and collaboration with their peers and to help them in memorize facts and information better. Games can be our best aid to turn the information into meaningful content.